Food avoidance in an Australian adult population sample: the case of dairy products. Issue 9 (20th November 2015) - Yantcheva, Bella; Golley, Sinéad; Topping, David; Mohr, Philip
Abstract: Objective: To assess the prevalence of and explanations for the avoidance of dairy foods, including symptoms attributed to their consumption, diagnoses and psychological predictors of avoidance. Also considered were comparisons with symptom-related avoidance of wheat in the same sample. Design: Cross-sectional population survey. Setting: The study was conducted in Australia using a national postal omnibus survey. Subjects: Adults aged 18 years and over ( n 1184; 52·9 % female) selected at random from the Australian Electoral Roll. Results: Despite few claims of formally diagnosed allergy or intolerance, 11·8 % of the sample reported avoiding dairy products because of adverse physiological effects, which commonly included gastrointestinal symptoms. Unlike wheat (3·5 %) or wheat-and-dairy (3·6 %) avoidance, dairy avoidance (8·2 %) was predicted by age (negatively) and worry about illness (positively). Conclusions: The findings are further evidence of a widespread tendency for consumers to exercise control over their health by eliminating dietary factors considered suspect without medical evidence or oversight. Unanswered questions include the decision processes underlying dairy avoidance, whether symptoms are attributed correctly, the agents and physiological mechanism(s) involved, the relative contributions of symptom severity and vigilance to the association with illness worry, and the nutritional adequacy of dairy avoiders' diets. Irrespective of the accuracy of self-diagnoses, if the elimination of suspect foods is an end in itself the paradoxical possibility for nutritional imbalances may have significant public health implications.